Meet The Authors (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1952)
Fred D. DeVaney (Magnetic Roasting of Iron Ores, P. 1219) has presented several other AIME papers, all of them concerned with grinding and concentrating problems. He is chief metallurgist, Pickands Mather & Co., at Hibbing Minn., after working for the U. S. Bureau of Mines at Tuscaloosa, Ala., and Rolla, Mo., as a junior metallurgist and a metallurgist. DeVaney started as a research metallurgist with Pickands Mather in 1942. He set up the first laboratory in the Lake Superior district devoted to taconite concentra¬ [ ] tion, his major interest. He has been an AIME member since 1923, holding various offices, including the first presidency of the Minnesota Section. DeVaney has a Bachelor's in Mining, and Master of Science earned at the University of Alabama in 1924. He is a member of the Engineers Club of Northern Minnesota and plays golf for relaxation and enjoyment.